1992
DOI: 10.1083/jcb.117.6.1263
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a human kinesin heavy chain gene: interaction of the COOH-terminal domain with cytoplasmic microtubules in transfected CV-1 cells

Abstract: Abstract. To understand the interactions between the microtubule-based motor protein kinesin and intracellular components, we have expressed the kinesin heavy chain and its different domains in CV-1 monkey kidney epithelial cells and examined their distributions by immunofluorescence microscopy. For this study, we cloned and sequenced cDNAs encoding a kinesin heavy chain from a human placental library. The human kinesin heavy chain exhibits a high level of sequence identity to the previously cloned invertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
150
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 67 publications
(88 reference statements)
10
150
0
Order By: Relevance
“…This band was absent from IPs containing GFP alone. Scale-up of the IPs and analysis by mass spectrometry revealed that the 120-kDa band contained Kif5B, the heavy-chain subunit of kinesin-1 [also known as conventional kinesin or KIF5 (32)]. Parallel yeast two-hybrid analysis (33), using a membrane proximal region of Nesp4 (residues 129-339) as bait, was performed by Myriad Genetics.…”
Section: Resultsmentioning
confidence: 99%
“…This band was absent from IPs containing GFP alone. Scale-up of the IPs and analysis by mass spectrometry revealed that the 120-kDa band contained Kif5B, the heavy-chain subunit of kinesin-1 [also known as conventional kinesin or KIF5 (32)]. Parallel yeast two-hybrid analysis (33), using a membrane proximal region of Nesp4 (residues 129-339) as bait, was performed by Myriad Genetics.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal kinesin-1 tail can bind ribonucleoprotein cargoes (26) and has a nucleotide-independent MT-binding activity that may facilitate kinesin-1's MT transport/sliding function (27)(28)(29)(30). All these distinct apparatuses are located near the critical autoregulatory region of the KHC tail.…”
mentioning
confidence: 99%
“…The tail HM site can also bind MTs independent of the head (28). It has been suggested that MT binding by the tail allows kinesin-1 to slide and organize MT arrays (27,29,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal kinesin heavy chain (nKHC) is encoded by a gene distinct from the one specifying the ubiquitous kinesin heavy chain (uKHC), although the two proteins share a 65% amino acid sequence identity and a very similar domain organization (Niclas et al, 1994). Both their molecular structures show an N-terminal motor domain (Yang et al, 1989;Nakata and Hirokawa, 1995), an a-helical coiled coil rod (De Cuevas et al, 1992), and a small Cterminal globular domain that, despite its still unclear function, is thought to be involved in the interaction with intracellular cargo (Navone et al, 1992;Toyoshima et al, 1992;Andrews et al, 1993;Skoufias et al, 1994;Yu et al, 1995). The sequence of nKHC has the unique feature of a 70-amino-acid C-terminal stretch that is absent in the uKHC sequence (Niclas et al, 1994).…”
mentioning
confidence: 99%